Penerapan Hibrid Sistem Biofilter dan Hidroponik Sebagai Alternatif Pengolahan Limbah Pemukiman Low Income People - Tumpal; Haryati Bawole Sutanto (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2019)
Domestic wastewater will cause environmental problems, if there is no treatment either communally or household scale or in other words, the people directly dispose of their waste into water bodies. There are several environmentally friendly and fairly inexpensive waste treatment systems, namely the biofilter system. The processing of the wastewater with a biofilter system in several studies resulted in very good reduction of some parameters. This research does not only use biofilter, because it is possible there are still residual inorganic compounds such as nitrate and phosphate left over from processing biofilter systems. So that a tertiary treatment is still needed using a hydroponic system. The results of this study, namely the tertiary treatment system with hydroponics can reduce the residual anoganic compounds of phosphate, such as the outlets of kangkung (76.13%), spinach (44.9%) and lettuce (45.95%), while nitrates did not decrease. The parameters of TDS, TSS, COD and BOD were reduced with the efficiency removal of 15.15-19.60%, 51.20-88.52%, 49.00-63,27% and 30.49-58.68% respectively.